IMPACT OF THE COVID-19 PANDEMIC ON REGENCY/ CITY REGIONAL ORIGINAL REVENUE IN THE SPECIAL REGION OF YOGYAKARTA - Linda Rohyani; Rudy Badrudin (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
This study aims to determine the impact of the Covid-19 pandemic on Regency/ City Regional Original Revenue in the Special Region of Yogyakarta. This type of research is quantitative research with secondary data taken by cluster sampling method. The analytical method used is parametric statistics, namely Two-Way Anova, and non-parametric statistics, namely the Wilcoxon-Rank Sum Test and the Kruskal-Wallis Test. The results showed that there were differences in the average Regional Original Revenue (PAD) of regencies/cities in DIY before and during the Covid-19 pandemic, and there were differences in average PAD between four regencies and one city in DIY before and during the Covid-19 pandemic.